Islamic capital markets : theory and practice - Krichene, Noureddine (New York : Wiley, 2012)
A comprehensive look at the essentials of Islamic capital markets Bringing together theoretical and practical aspects of capital markets, Islamic Capital Markets offers readers a comprehensive insight into the institutions, instruments, and regulatory framework that comprise Islamic capital markets. Also exploring ideas about money, central banking, and economic growth theory and their role in Islamic capital markets, the book provides students and practitioners with essential information about the analytical tools of Islamic capital markets, serves as a guide to investing in I.
The Valuation of Securities, Leverage, and the Cost of Capital: The Modigliani and Miller TheoryWeighted Average Cost of Capital; Implications of the Capital Cost Analysis for the Theory of Investment: Capital Structure and Investment Policy; The Agency Problem; Summary; References; Questions; Chapter 6: Asset Pricing under Uncertainty; Modeling Risk and Return; Market Efficiency and Arbitrage-Free Pricing; Basic Principles of Derivatives Pricing; Summary; References; Questions; Chapter 7: The Consumption-Based Pricing Model; Intertemporal Optimization and Implication to Asset Pricing
Print version record.
Keywords: Investments -- Religious aspects -- Islam; Investments -- Islamic countries; Banks and banking -- Islamic countries; Capital market -- Islamic countries; Financial instruments -- Islamic countries; Finance (Islamic law); Bonds -- Islamic countries; BUSINESS & ECONOMICS -- Investments & Securities -- General; Banks and banking; Bonds; Capital market; Finance (Islamic law); Financial instruments; Investments, Islamic country; Investments -- Religious aspects -- Islam; Islamic countries; Electronic books